Sensitivity of the Trade Openness in Nepal - Chaudhary, Shashi Kant (NRB Economic Review, 2011)
In this paper, Openness Growth Monitoring (OGM) Model is applied to examine the various aspects of trade openness like vulnerability, sensitivity and harmonization as well as the impact of trade openness on per capita income growth for the period of 1990/91 to 2010/11. The results suggest that overall trade openness vulnerability of Nepal is low with the manufacturing and service sector being more open in comparison to the agriculture and energy sectors. While there is strong performance of the openness growth rate for the review period, the average ratio of the openness growth and per capita income growth both with nominal income, is negative. The results indicate low sensitivity of per capita income growth to the trade openness growth. The findings reveal that the productivity benefits from additional trade are higher for the trading partners of Nepal than itself. Hence, it is argued that Nepal has liberalized trade without introducing appropriate internal policies and institutions.